2022
DOI: 10.1002/jcp.30936
|View full text |Cite
|
Sign up to set email alerts
|

LEP and LEPR are possibly a double‐edged sword for wound healing

Abstract: Wound healing is a complex and error‐prone process. Wound healing in adults often leads to the formation of scars, a type of fibrotic tissue that lacks skin appendages. Hypertrophic scars and keloids can also form when the wound‐healing process goes wrong. Leptin (Lep) and leptin receptors (LepRs) have recently been shown to affect multiple stages of wound healing. This effect, however, is paradoxical for scarless wound healing. On the one hand, Lep exerts pro‐inflammatory and profibrotic effects; on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 123 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…Some other MSC markers have also been demonstrated, such as LepR (Leptin receptor) [270][271][272][273], CD34 [274][275][276], and TNFRSF10D [277]. However, their functions in MSCs remain unclear.…”
Section: Other Markersmentioning
confidence: 99%
“…Some other MSC markers have also been demonstrated, such as LepR (Leptin receptor) [270][271][272][273], CD34 [274][275][276], and TNFRSF10D [277]. However, their functions in MSCs remain unclear.…”
Section: Other Markersmentioning
confidence: 99%
“…Besides regulating food intake and body weight, LEP and leptin receptors (LEPRs) also play an integral role in fetal growth, proinflammatory immune responses, angiogenesis and lipolysis. [36][37][38] Accordingly, elevated levels of LEP during lung inflammation and the presence of functional LEPR in the lungs suggest that LEP/LEPR play an important role in respiratory immune responses and the development of inflammatory respiratory diseases. 39 Among patients with moderate COPD, Broekhuizen et al 40 found that leptin levels were detected in induced sputum and were significantly correlated with C-reactive protein and total TNF-α.…”
mentioning
confidence: 99%